Characterisation of the Aroma of the Hybrid Ferdinand de Lesseps (Vi tis vinifera x Vi tis labrusca) - Rogers, I.M.; van Wyk, C.J. (South African Journal of Enology and Viticulture, 2017)
Freon 11-extracted volatiles of Ferdinand de Lesseps grape juice were studied by capillary gas chromatography, capillary gas chromatography-mass spectrometry and gas chromatography-sniffing. The berries were crushed under an inert atmosphere and the juice extracted with Freon 11 for 20 hours. Thirty-one compounds were reported. The juice was quantitatively characterised mostly by esters, particularly hydroxy esters. These esters are most probably responsible for the sweetish pineapple aroma of Ferdinand de Lesseps grapes whereas o-aminoacetophenone and 2,5-dimethyl-4-hydroxy-3(2H)-furanone could contribute to its hybrid note.